(untitled) (Research, Society and Development, 2025)
Fetal macrosomia, defined as the birth of a newborn weighing 4,000 g or more or above the 90th percentile for gestational age, represents a significant obstetric challenge due to its impact on maternal and neonatal morbidity and mortality. This study aimed to identify the main maternal determinants of fetal macrosomia, analyze possible interactions between risk factors, and discuss neonatal outcomes and preventive strategies. An integrative literature review was conducted using national databases. The findings indicate that gestational diabetes, maternal obesity, excessive gestational weight gain, advanced maternal age, multiparity, tall maternal stature, post-term pregnancy, and male fetal sex are the primary associated factors. Furthermore, the coexistence of these factors exerts a synergistic effect, substantially increasing the risk of macrosomia. The most common neonatal complications include shoulder dystocia, hypoglycemia, birth trauma, polycythemia, and a higher incidence of cesarean delivery, in addition to an increased predisposition to metabolic disorders during childhood and adulthood. Preventive strategies involve strict glycemic control, appropriate monitoring of maternal weight gain, ultrasonographic surveillance of fetal growth, and individualized obstetric management. It is concluded that reducing the incidence and complications of fetal macrosomia requires integrated actions involving high-quality prenatal care, health education, and evidence-based interventions.